Cash Ratio, Debt to Equity Ratio, Return on Asset, Firm Size, Growth dan Dividen Payout Ratio Pada Perusahaan Manufaktur di Indonesia - Lanawati Lanawati; Amilin Amilin (Magister Akuntansi Universitas Pancasila, 2015)
A B S T R A C T This study aimed to examine the effect of the cash ratio , debt to equity ratio , return on assets and firm size growth of the dividend payout ratio. Samples were tested as many as 118 data for companies that consistently pay dividends for 5 years from 2008 until 2012. The tests were conducted with a multiple regression test . The results show that the return on assets affect the dividend payout ratio. while cash ratio , debt to equity ratio and firm size growth has no effect. Research to be dating should pay attention to the changes associated with the assessment and recognition of the accounts in the financial statements in order to obtain better results. A B S T R A K Penelitian ini bertujuan untuk menguji pengaruh cash ratio, debt to equity ratio, return on asset dan pertumbuhan ukuran perusahaan dari rasio pembayaran dividen. Sampel diuji sebanyak 118 data perusahaan yang konsisten membayar dividen selama 5 tahun dari 2008 sampai 2012. Pengujian dilakukan dengan uji regresi berganda. Hasil penelitian menunjukkan bahwa pengembalian aset mempengaruhi rasio pembayaran dividen. sementara rasio kas, rasio hutang terhadap ekuitas dan pertumbuhan ukuran perusahaan tidak berpengaruh. Penelitian yang akan berkencan harus memperhatikan perubahan yang terkait dengan penilaian dan pengakuan dari akun dalam laporan keuangan untuk memperoleh hasil yang lebih baik. JEL Classification: G14, G30